The Impact of Lifestyle, Brand Image, Customer Review, COD Feature, And Flash Sale on Skincare Product Purchases Among General Z Consumers Through Shopee In Belongkut Village - Ritonga, Nur Asia; Nasution, Ade Parlaungan; Pohan, Muhammad Yasir Arafat (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the influence of lifestyle, brand image, customer reviews, cash on delivery, and flash sale features on skincare product purchasing decisions among Gen Z customers through Shopee in Belongkut village. This study used a quantitative methodology with a purposive sampling technique involving 96 participants. Data were collected through a Likert scale questionnaire, and the analysis included validity assessment, reliability evaluation, verification of classical assumptions, multiple linear regression analysis, evaluation of the coefficient of determination (R²), and partial (t-test) and simultaneous (F-test) hypothesis testing. The results showed that lifestyle factors, brand image, customer reviews, cash on delivery (COD) features, and flash sale significantly influenced purchasing decisions. The five independent variables significantly influenced purchasing decisions, evidenced by an F value of 83.130 and a significance level of 0.000. The coefficient of determination (R²) score of 0.822 indicated that 82.2% of the variance in purchasing decisions was explained by this research model. These findings have implications for e-commerce entities in formulating effective marketing strategies targeting Gen Z customers in rural areas.